2021
DOI: 10.1016/j.rasd.2021.101859
|View full text |Cite
|
Sign up to set email alerts
|

Autism assessment via telehealth during the Covid 19 pandemic: Experiences and perspectives of autistic adults, parents/carers and clinicians

Abstract: Background The COVID-19 pandemic has seen a rapid increase in the use of telehealth to deliver services to autistic individuals and their families. Research into the provision of autism assessments via telehealth is limited and few studies have explored clinician perspectives of conducting diagnostic assessments for autism in this way. The objective of this study was to examine the acceptability of a new telehealth model from the perspective of key stakeholder groups in an Australian community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
5
30
1
Order By: Relevance
“…As telehealth is preferred by some patients, a logical step may be for autism diagnostic services to offer choice about whether an assessment will be conducted via telehealth, in person or with a hybrid approach. That said, there are clearly issues with parity of service provision; for example, findings reported here and elsewhere [e.g., ( 18 , 22 , 23 )] indicate telehealth may not be offered to all (e.g., due to clinical presentation or risk), or cannot be offered to all (e.g., due to a lack of internet access). Further evaluation is therefore needed, such as with quality improvement projects, qualitative interviews or focus groups, to establish how to enhance accessibility.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…As telehealth is preferred by some patients, a logical step may be for autism diagnostic services to offer choice about whether an assessment will be conducted via telehealth, in person or with a hybrid approach. That said, there are clearly issues with parity of service provision; for example, findings reported here and elsewhere [e.g., ( 18 , 22 , 23 )] indicate telehealth may not be offered to all (e.g., due to clinical presentation or risk), or cannot be offered to all (e.g., due to a lack of internet access). Further evaluation is therefore needed, such as with quality improvement projects, qualitative interviews or focus groups, to establish how to enhance accessibility.…”
Section: Discussionmentioning
confidence: 72%
“…Overall, ~60% of participants reported feeling confident to assess and diagnose autism remotely. However, as in the study by Gibbs et al ( 23 ), and Matthews et al ( 22 ), there were some consistent problems identified that could impact on the diagnostic process, including technological challenges, poor internet access, environmental challenges (e.g., that the home environment did not seem a suitable place to assess patients) and difficulties with engaging families/carers and/or patients.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations